2022
DOI: 10.3390/ejihpe12060046
|View full text |Cite
|
Sign up to set email alerts
|

The Network That Unites a Qualitative Study on Clinical Psychological Intervention for Women with a History of Breast Cancer and Chronic Pain

Abstract: The aim of this qualitative research is to deepen the knowledge in the field of psycho-oncology and the consequences of chronic and persistent pain by listening to patients’ experiences, their emotions and difficulties in facing this hard condition, and assessing their perception of the role of the psychologist in pain management. In this qualitative study, a semistructured interview was used, designed from three research questions: chronic pain and quality of life; chronic pain and psychological well-being; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although major depressive disorder represents the most common comorbidity [5], it has been found that the comorbidity of anxiety is also usual [26]. Further research is still necessary in the context of palliative care, which implies that loss of a loved one occurs after a chronic condition, where the family members face a stressful situation [27]. Also of particular interest is the role of anxiety and depression in discriminating individuals with PGD with adequate accuracy, in terms of sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Although major depressive disorder represents the most common comorbidity [5], it has been found that the comorbidity of anxiety is also usual [26]. Further research is still necessary in the context of palliative care, which implies that loss of a loved one occurs after a chronic condition, where the family members face a stressful situation [27]. Also of particular interest is the role of anxiety and depression in discriminating individuals with PGD with adequate accuracy, in terms of sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…They also experience loss of hair and nails due to complications and side effects associated with cancer treatments [9,10]. Furthermore, they may have problems doing household chores or working at their workplaces due to physical pain [11]. Early breast cancer patients experience various stressors as their overall quality of life deteriorates [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Women with breast cancer also have lower sexual quality of life due to negative body image, physical inactivity, depression, sleep problems, chest symptoms, and chronic fatigue [16]. Therefore, their quality of life should include consideration of their psychological, physical, and living characteristics [11].…”
Section: Introductionmentioning
confidence: 99%